The degradation of allyl isothiocyanate and its impact on methane production from anaerobic co-digestion of kitchen waste and waste activated sludge - Qin, Yu; Yang, Jingnan; Wu, Yanxin; Wang, Dongbo; Liu, Xuran; Du, Mingting; He, Dandan; Yi, Neng (Bioresource technology, 2022)
[Display omitted] •AITC was degraded by –NCS and CC–C– isomerization in anaerobic co-digestion.•AITC inhibited methane production from anaerobic co-digestion of KW and WAS.•AITC inhibited acetotrophic methanogenesis by reducing the activity of AK enzyme.•AITC enriched complex organic degradation microbes such as Bacillus. Producing methane from anaerobic co-digestion of kitchen waste and waste activated sludge has been widely implemented in real-world situations. However, the fate and impact of allyl isothiocyanate (AITC), a main active component in cruciferous vegetables, in the anaerobic co-digestion has never been documented. This study therefore aims to provide such supports. Experimental results exhibited that AITC was degraded completely by microorganisms and served as a substrate to produce methane. As AITC increased from 0 to 60 mg/L, the maximum methane production decreased from 285.1 to 35.8 mL/g VS, and the optimum digestion time was also prolonged. The mechanism study demonstrated that AITC induced cell apoptosis by modifying the physicochemical properties of cell membrane, which resulted in inhibitions to the procedure of anaerobic co-digestion. The high-throughput sequencing showed that AITC enriched the microorganism for degradation of complex organic compounds such as Bacillus, but lessened anaerobes involved in hydrolysis, acidogenesis, and methanogenesis.